2016
DOI: 10.1097/cin.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Computer Literacy of Nurses in Lesotho

Abstract: Health systems worldwide are moving toward use of information technology to improve healthcare delivery. However, this requires basic computer skills. This study assessed the computer literacy of nurses in Lesotho using a cross-sectional quantitative approach. A structured questionnaire with 32 standardized computer skills was distributed to 290 randomly selected nurses in Maseru District. Univariate and multivariate logistic regression analyses in Stata 13 were performed to identify factors associated with ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…The results of this study corroborate with other studies on student nurses which indicate that young female adults make up the largest proportion of nursing students (Mugomeri et al 2016 :530; Yigzaw et al 2015 :133).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study corroborate with other studies on student nurses which indicate that young female adults make up the largest proportion of nursing students (Mugomeri et al 2016 :530; Yigzaw et al 2015 :133).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have identified the need to bridge the digital skill gap of healthcare providers in order to transfer technology to the point where health service quality is maintained. However, most of these studies do not specify in detail where the critical digital skill gap lays [ 19 21 ]. By itself, digital literacy is a congregating and evolving concept through time and advancement in technology.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses working in paediatrics, as well as those working in TB and HIV management, had more opportunities to work with computers and EHR systems. In contrast, Mugomeri et al (2016) reported that the majority of nurses in Lesotho were found to have inadequate computer skills. This was attributed to the many years that had passed since the nurses obtained their latest qualification and the lack of accessibility to computers in their work environment.…”
Section: Discussionmentioning
confidence: 96%
“…The EHR challenges reported include lack of computer skills, poor infrastructure, and poor implementation strategies (Ajiboye, Adekoya, Alawiye, & Oyedipe, 2014;Odekunle, Odekunle, & Shankar, 2017). Although healthcare systems around the globe are geared towards using EHRs to enhance healthcare delivery, Mugomeri, Chatanga, Maibvise, & Masitha (2016) highlight that this is only possible if healthcare workers possess the fundamental computer skills. According to Alwan, Awoke, & Tilahun (2015), the current skill level of healthcare professionals is one of the most common obstacles to the adoption of EHR systems in health care.…”
Section: Introductionmentioning
confidence: 99%